Overriding Lithospheric Strength Affects Continental Collisional Mode Selection and Subduction Transference: Implications for the Greater India–Asia Convergent System - Li, Qian; Li, Zhong-Hai; Zhong, Xinyi (Frontiers in Earth Science, 2022)
The India–Asia collision, starting from 55 ± 5 Ma, leads to the formation of the Himalayas and Tibetan Plateau with great gravity potential energy and large forces acting on the surrounding blocks. However, the subduction transference/jump does not occur in the southern Indian continental margin or the northern Indian oceanic plate as supposed to happen repeatedly during the preceding Tethys evolution. Instead, the continental collision and orogeny continues until present day. The total amount of convergence during the India–Asia collision has been estimated to be ∼2,900–4,000 km and needs to be accommodated by shortening/extrusion of the Tibetan plate and/or subduction of the Greater Indian plate, which is a challenging issue. In order to study the collision mode selection, deformation partition, and continental mass conservation, we integrate the reconstruction-based convergence rate of the India–Asia collision into a large-scale thermomechanical numerical model and systematically investigate the effects of overriding Tibetan lithospheric strength and the amount of convergence. The model results indicate that the absence of subduction transference during the India–Asia collision may be attributed to strain localization and shortening of the rheologically weak Tibetan plate. In case of the India–Asia collision for ∼50 Myr with a total convergence of ∼2,900 km, the model with the intermediately weak Tibetan plate could reconcile the general deformation partition and continental mass balance of the Himalayan–Tibetan system. However, the longer period of India–Asia collision for ∼55 Myr leads to significant shortening of the overriding plate that is not consistent with the Tibetan observations, in which case an oceanic basin may be required for the Greater Indian continent.